Magpie Trial in the UK: methods and additional data for women and children at 2 years following pregnancy complicated by pre-eclampsia - Armstrong Nina; Spark Patsy; Smyth Rebecca MD; Duley Lelia (BMC, 2009)
Abstract Background The Magpie Trial, a randomised trial comparing magnesium sulphate with placebo for women with pre-eclampsia. This paper describes methods used for follow up in the UK, and presents additional data collected. Methods In the UK 774 women and their 827 children were included; excluded were women discharged without a surviving child and families who opted out. General practitioners were sent a questionnaire when the child was around 18 months old. When the child was two years, or older, questionnaires asking about the health of the women and children were posted to families. A sample of families was offered a home visit, during which the child was assessed using the Bayley Scales of Infant Development. Results Of the women, 12 were lost to follow up and three died. Of the children, 12 were lost to follow up, 5 were excluded and 19 died. General practitioners returned 688/759 (91%) questionnaires, as did 619/759 (82%) women. Responses were largely comparable. 32 women had serious morbidity potentially related to pre-eclampsia. 30% of children were reported to have been admitted to hospital. There were no clear differences between the randomised groups in the child's behaviour, women's fertility or use of health service resources. Conclusion Data presented here provide further reassurance about the longer term safety of magnesium sulphate when used for women with pre-eclampsia. Postal questionnaires in the UK to assess the longer term health and wellbeing of women and children recruited to trials are feasible, and can achieve a high response rate. Responses from families and general practitioners were comparable Trial registration Trial registration number of the Magpie Trial [ISRCTN86938761]